The role of evaluation in successful integrated natural resource management - Twomlow, Stephen; Lilja, Nina (Crop Sciences Congress, 2004)
Evaluating the impact of NRM research is essential. This paper suggests that a key to evaluation of NRM research is the mindset of the researchers. We discuss the contribution of four factors to a reflective learning process necessary in integrated NRM: stakeholder participation, systems approach to evaluation, timing of evaluation and an interative approach.